2020
DOI: 10.1016/j.jvs.2019.04.482
|View full text |Cite
|
Sign up to set email alerts
|

Migration and sac expansion as modes of midterm therapeutic failure after endovascular aneurysm sealing

Abstract: Background: Endovascular aneurysm sealing (EVAS) is a disruptive technology to treat abdominal aortic aneurysm (AAA). The use of sac filling rather than endograft fixation was designed to treat aortic aneurysms in a wide range of morphologic appearances and to reduce endoleaks. There are few data reporting outcomes beyond postoperative follow-up. This study reports outcomes up to 5 years for Nellix (Endologix, Irvine, Calif) EVAS. Methods: Data were prospectively collected for EVAS patients from the time of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…As such, the study could be underpowered, and results must be interpreted with caution. Stenson et al 23 showed high technical failure rates of chEVAS past 3 years, which was not available in our follow-up. The only 2 cases of clinically significant migration, our primary endpoint, occurred 3 years after the index procedure.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As such, the study could be underpowered, and results must be interpreted with caution. Stenson et al 23 showed high technical failure rates of chEVAS past 3 years, which was not available in our follow-up. The only 2 cases of clinically significant migration, our primary endpoint, occurred 3 years after the index procedure.…”
Section: Discussionmentioning
confidence: 67%
“…A comparison with other studies is complicated by inconsistent definitions of migration. Stenson et al 23 recently published an analysis including 79 cases of chEVAS of which 57 were performed in an elective setting. They reported freedom from migration (≥5 mm) of 100% at 1 year and 85.7% at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…22 In the absence of proximal or distal fixation, the endobags could dislodge during routine activities of daily living, which was predictable from mathematical modeling. With further emerging data regarding midterm EVAS failure, 23 it is important to understand the regulatory processes involved in bringing a new medical device to market.…”
mentioning
confidence: 99%
“…So far, only a few studies have reported outcomes after primary EVAS beyond postoperative follow-up. 29 Stenson et al collected outcomes from a series of 295 EVAS with a median follow-up of 2.42 years and reported a therapeutic failure in 33.2% of cases, with the need of a secondary procedure in 5.36% of cases. Early encouraging results of the EVAS as a primary procedure have been eroded, and the recent loss of the CE mark of the device may limit further studies to address its interest to treat failed EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies have reported outcomes after primary EVAS beyond postoperative follow-up. 29 Stenson et al. collected outcomes from a series of 295 EVAS with a median follow-up of 2.42 years and reported a therapeutic failure in 33.2% of cases, with the need of a secondary procedure in 5.36% of cases.…”
Section: Discussionmentioning
confidence: 99%